Intensity of Ground Cover Crop Arachis pintoi, Rhizobium Inoculation and Phosphorus Application and Their Effects on Field Growth and Nutrient Status of Cocoa Plants - John Bako Baon; John Pudjiono (Indonesian Coffee and Cocoa Research Institute, 2006)
Arachis pintoiis potentially as a cover crop for cocoa (Theobroma cacaoL.) farm, however information regarding its effect on the growth of cocoa plants in the field is very limited. The objective of this experiment is to investigate the combined influence of ground cover crop A. pintoi, rhizobial bacterial inoculation and phosphorus (P) fertilizer on the growth of cocoa in the field and nutrient status. This experiment laid out in split-split plot design consisted of three levels of cover crop (without, A. pintoiand Calopogonium caeruleum), two levels of rhizobium inoculation (not inoculated and inoculated) and two levels of phosphorus application (no P added and P added). The results showed that in field condition the presence of A. pintoias cover crop did not affect the growth of cocoa. On the other hand, C. caeruleumas cover crop tended to restrict cocoa growth compared to A. pintoi. Application of P increased leaf number of cocoa plant. Biomass production of A. pintoiwas 40% higher than C. caeruleum. Soil organic carbon and nitrogen contents were not affected by ground cover crops, though higher value (0.235% N and 1.63% organic C) was obtained from combined treatments of inoculation and P addition or neither inoculation nor P addition. In the case of no rhizobium inoculation, soil N content in cocoa farm with A. pintoicover crop was lower than that of without cover crop or with C. caeruleum. Cover crop increased plant N content when there was no inoculation, on the other hand rhizobium inoculation decreased N content of cocoa tissue. Tissue P content of cocoa plant was not influenced by A. Pintoicover crop or by rhizobium inoculation, except that the P tissue content of cocoa was 28% higher when the cover crop was C. caeruleumand inoculated. Key words : Arachis pintoi, Theobroma cacao, Calopogonium caeruleum, rhizobium, nitrogen, phosphorus.